2021
DOI: 10.3390/medicines8090046
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Strategies to Avoid Medication Errors and Improving Reporting Systems

Abstract: Background: Population-based studies from several countries have constantly shown excessively high rates of medication errors and avoidable deaths. An efficient medication error reporting system is the backbone of reliable practice and a measure of progress towards achieving safety. Improvement efforts and system changes of medication error reporting systems should be targeted towards reductions in the likelihood of injury to future patients. However, the aim of this review is to provide a summary of medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 49 publications
0
31
0
2
Order By: Relevance
“…In addition, they often need to play the role of an expert in prescribing the right drug for the right patient with the right dose via the right route of administration ( Maxwell, 2016 ). While there are multiple factors that contribute to MEs ( Mutair et al, 2021 ), these are reduced in high-risk situations if they are properly educated, trained, and equipped to prevent such medicine-related harms ( Wittich et al, 2014 ). Consequently, their knowledge regarding administration, regulations, and practices related to HAMs is of considerable importance to prevent HAMs-related errors among patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they often need to play the role of an expert in prescribing the right drug for the right patient with the right dose via the right route of administration ( Maxwell, 2016 ). While there are multiple factors that contribute to MEs ( Mutair et al, 2021 ), these are reduced in high-risk situations if they are properly educated, trained, and equipped to prevent such medicine-related harms ( Wittich et al, 2014 ). Consequently, their knowledge regarding administration, regulations, and practices related to HAMs is of considerable importance to prevent HAMs-related errors among patients.…”
Section: Introductionmentioning
confidence: 99%
“…The Five Moments for Medication Safety tool was valued by patients and should be used in practice, according to an exploratory descriptive study by (Subakumar et al 2020) 83 percent of patients said the tool was very useful, and healthcare professionals need to play a role in engaging patients and helping them integrate the questions into consultations. (Mutair et al, 2021) asserted that for the medication usage process to progress into a safer practice, health care organizations must adopt a successful atmosphere. Inconsistent with these ndings (Dijkstra et al, 2021) Develop a competency framework for nurses in pharmaceutical care and indicate that future research should focus on incorporating these capabilities in nurse education.…”
Section: Resultsmentioning
confidence: 99%
“…Also, by encouraging the use of medication error reporting systems more insight could be gained into the extent and impact of medication-related harm to reduce MRRs. Previous studies showed a high proportion of underreporting of medication errors (approximately 50–60%) among healthcare providers ( Jember et al, 2018 ; Mutair et al, 2021 ). However, Elden et al found a decrease of approximately 50% of medication errors (from 6.7 to 3.6%, p ≤ 0.001) through application of error reporting among healthcare providers ( Elden and Ismail, 2016 ).…”
Section: Discussionmentioning
confidence: 98%